2020
DOI: 10.1089/fpsam.2019.0003
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Level of Evidence Trends in Facial Plastic Surgery Research

Abstract: Background: Knowledge of the quality of evidence in facial plastic surgery research is essential for the implementation of evidence-based practices. The purpose of this study is to provide an update over the past decade as to whether the level of evidence in leading journals featuring topics in facial plastic surgery has changed in comparison with prior reports. Materials and Methods: This study is a systematic review, designed to evaluate the level of evidence observed in the facial plastic surgery literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…In otology, there was an increasing proportion of high‐level evidence studies between 1997 and 2017, from 11.4% to 24.3% 12 . The subspecialty of facial plastics and reconstructive surgery reported an increase in the proportion of level II evidence, from 10.6% to 18.1%, and a decrease in the proportion of level IV evidence, from 47.7% to 35.8%, among articles published between 2008 and 2019 11,22 . However, the current study focusing on pediatric OTL‐HNS found that articles from 1996 to 2016 do not follow this same trend as the proportion of high‐quality publications remained stable at approximately 30%.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…In otology, there was an increasing proportion of high‐level evidence studies between 1997 and 2017, from 11.4% to 24.3% 12 . The subspecialty of facial plastics and reconstructive surgery reported an increase in the proportion of level II evidence, from 10.6% to 18.1%, and a decrease in the proportion of level IV evidence, from 47.7% to 35.8%, among articles published between 2008 and 2019 11,22 . However, the current study focusing on pediatric OTL‐HNS found that articles from 1996 to 2016 do not follow this same trend as the proportion of high‐quality publications remained stable at approximately 30%.…”
Section: Discussioncontrasting
confidence: 61%
“…However, the current study focusing on pediatric OTL‐HNS found that articles from 1996 to 2016 do not follow this same trend as the proportion of high‐quality publications remained stable at approximately 30%. As with other otolaryngology subspecialties, the current study also identified that high‐quality papers continue to represent a minority of total research 10–12,22 …”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations